The Influence of Harvested Area, Rice Consumption on Rice Crop Production in Makassar City - Asriadi, Andi Amran; Firmansyah, Firmansyah (Baselang, 2023)
One of the basic needs for agricultural products is rice. In Indonesia, rice is the most important food for the development of the country's economy because rice is the most important staple food in this country, covering more than half of the population. The aim of the research is to find out how much influence the harvest area (X1), rice consumption (X2) has on rice crop production (Y) in Makassar City, South Sulawesi. Secondary data was obtained through the South Sulawesi Central Statistics Agency (BPS). The method used is multiple linear regression analysis in the Cobb-Douglas function using the SPSS version 22 program. The research results show that harvest area (X1) partially has a negative and significant effect on production. Meanwhile, rice consumption (X2) partially has a positive and significant effect on production. Indonesian people's recommendations must also be balanced with rice production and consumption that can meet food needs.